Priority Programs for Rungan Watershed Management: A Comprehensive and Participatory Approach - Endy; I Nyoman Sudyana; Herwin Sutrisno; Raden Mas Sukarna (Jurnal Penelitian Pendidikan IPA, 2026)
The watershed has a strategic role in maintaining hydrological balance, ecosystem integrity, and community welfare. However, the Rungan watershed is under threat from deforestation and ecosystem damage, therefore a study is needed that considers all related aspects as the basis for making a management strategy for the Rungan watershed. This study aims to find out the priority problems faced by the Watershed Rungan and the aspects of its causes. Furthermore, this research also seeks to formulate priority solutions that can overcome the problems faced by the Rungan watershed. Using qualitative and quantitative approaches, this study applies the Analytical Network Process (ANP) in formulating the priority strategy for the management of the Watershed.  This study found that ecological problems are considered the main problem. Alternative solutions that have been successfully formulated include ecological restoration, economic recovery, and institutional strengthening and coordination between stakeholders. Zoning regulation is a priority for area management and is the main strategy for the management of the Rungan watershed by regulating various programs such as forest rehabilitation, ecotourism, and environmentally friendly land use. For these programs to be carried out in a synergistic manner, it is necessary to coordinate and synergize programs between relevant stakeholders.